2020
DOI: 10.32530/agroteknika.v3i1.68
|View full text |Cite
|
Sign up to set email alerts
|

Perpindahan Panas pada Pengering Tipe Drum Berputar pada Kondisi Tanpa Beban

Abstract: Pengering tipe drum berputar yang dikembangkan merupakan sistem yang terdiri atas empat subsistem yaitu: tungku pembakaran, tangki air, penukar panas, dan silinder pengering. Penelitian ini bertujuan untuk mengetahui mekanisme pindah panas pengering tipe drum berputar, besarnya kehilangan panas, dan efisiensi termal sistem selama proses pengeringan tanpa beban. Metode penelitian yang digunakan adalah metode analitik pada pengering tipe drum berputar. Variabel penelitian meliputi: (a) variabel pengukura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…This phenomenon is attributed to the reduction in moisture content due to heating. Additionally, [24] confirms that an extended drying time leads to a decrease in the yield of herbal tea made from sungkai leaves, as the yield decreases with the prolonged drying duration.…”
Section: Estimation Of Shelf Lifesupporting
confidence: 58%
See 2 more Smart Citations
“…This phenomenon is attributed to the reduction in moisture content due to heating. Additionally, [24] confirms that an extended drying time leads to a decrease in the yield of herbal tea made from sungkai leaves, as the yield decreases with the prolonged drying duration.…”
Section: Estimation Of Shelf Lifesupporting
confidence: 58%
“…Investigations have shown that storage temperature and packaging type have a statistically significant impact on the yield of pegagan tea at a 5% significance level. As mentioned in [23], the reduction in yield persists with increasing temperature and longer drying durations during the drying process. This phenomenon is attributed to the reduction in moisture content due to heating.…”
Section: Estimation Of Shelf Lifementioning
confidence: 78%
See 1 more Smart Citation
“…Menurut Kavadya & Ropiudin, (2020) pindah panas adalah perpindahan energi yang diakibatkan oleh perbedaan suhu. Transfer energi sebagai panas merupakan suatu sistem yang memiliki suhu lebih tinggi berpindah ke sistem yang memiliki suhu yang lebih rendah (Hossain, 2011).…”
Section: Perpindahan Panasunclassified